Strategi Pemasaran Digital Terhadap Peningkatan Minat Beli Konsumen - Sigalingging, Trinita Estetika (Journal of Business Management Education (JBME), 2020)
Digital marketing such as online advertising is an important component for running a business. This study aims to determine what are the digital marketing strategies that can increase consumer buying interest. Through the literature, online advertising is used to inform products or services, and used to build relationships with potential consumers by communicating through the advertisements so that they can motivate in making purchasing decisions. The method used in this study is the type of library research. From this study, it can be concluded that digital marketing can increase consumer buying interest by paying attention to the layout, ease in closing advertisements, and givingÂ  vouchers or discounts. The implication of this research is as a material consideration for online businesses to produce advertisements that can positively influence consumer buying interest. The weakness of this study is that researchers cannot directly go to the field to get data.